Normas e vozes no CEFET Campos : convergências e divergências : uma leitura do texto tecido no interior da escola nos anos de 1994-1999 - Stelling, Luiz Felipe Pecanha (2004)
Rules and voices at CEFET Campos: convergences and divergences, reason of this study, was built as a kind of reading of the inside of Escola Técnica Federal de Campos in the years 1994-1999. To reach our aim we have researched the circulating discourses that were looking for hegemony and could be felt in the Institutional Project of CEFET Campos, in the legislation that was published in 1996 and 1997 referring to professional education and in the teachers´ voices, present in the school everyday context, performers` voices which lived in that period. The authors we have used as a theoretical base in the study were: Bakhtin, with his considerations concerning the principles of language philosophy in a Marxist point of view; Eagleton in the studies about Ideology; Konder and Bakhtin again in the relation between Ideology and Language. Through the linguistic intermediation we have tried to observe ideological conflicts, considering that `the word is able to register the most intimate and ephemeral transitory phases of changes`, in accordance with Bakhtin. From the methodological point of view, in the sense of ´ how to reveal the ideologies which can be present in the legislation`, the research was done considering the analysis of content, basing on Bardin and Triviños, and as a thesis has a non-conclusive characteristic, we have worked with Argumentation, considered as a research gender. In the studies we have done aiming at the understanding of teachers´attitude, we have highlighted ideological aspects that we have considered responsible by movable divergences and convergences, in those people´s discourses and we have also analyzed the evidences of the culture of submission that characterizes the Brazilian history (and professional education history) what leads us to the concept of `habitus`in Bourdieu.